Fermentation of Soybean Meal to Improve Diet Formulation for Common Carp Cyprinus carpio L. - Najim, Salah; Al-Noor , Jalal (Iraqi Journal of Aquaculture, 2026)
This investigation aimed to evaluate the chemo-biological fermentation of FSBM for partial substitution of SBM at ratios of (C 0%, T1 15%, T2 25%, and T3 35%) in diets formulated for common carp (Cyprinus carpio L.) juveniles. The FSBM contained 51.22% protein and 17 amino acids in varying proportions, including 10 essential amino acids, with Lysine having the highest value of 9.98 µg/100 µg protein. Growth parameters of the experimental fish were monitored for 56 days during which they were fed at 3% of their live body weight. Fish were weighed biweekly to adjust feed ration. Results showed that diet T2 had the highest values for initial weight, final weight, weight gain, relative growth rate, SGR, FCR and PER with values of 14.7 g, 31.4 g, 16.7 g, 113.6 %, 1.355%/day, 1.91 and 1.603 respectively. Control diet (C) achieved the lowest values with rates of 15.1, 25.9, 10.8, 71.5, 0.963, 2.83 and 1.078, respectively, with significant difference (p≤0.05) in comparison with other treatments. The highest total apparent digestibility coefficient 79.6 % was recorded in treatment T2 (25% supplementation), and the lowest recorded 75.7% with no supplementation treatment (control). The same trend was observed for the digestibility of protein, fat, ash and carbohydrate. From the results of Statistical analysis significant differences (p≤0.05) were revealed between supplementation treatments (T1, T2, and T3) when compared with control, except for fat and ash digestibility, where all treatments showed non-significant differences (p≥0.05). The results indicated that FSBM supplemented treatments (T1, T2, and T3) achieved better growth than control, where T2 diet clearly outperforming the other dietary treatments in measured nutrition and growth parameters.